(untitled) (Revista Inclusiones, 2019)
Relying on the results of the research conducted within the framework of the project “The sociopolitical dimension of the Eurasian integration”, the article provides an assessment of the condition of interethnic concord between citizens of the member states of the Eurasian Economic Union that live and work in the Moscow metropolis. The assessment is based on the analysis of the ideas about the goals and results of functioning of the Eurasian Economic Union, interest in the further development of integration processes, civic identity, interethnic attitudes, intergroup differentiation, and readiness to cooperate with citizens of the member states of the Eurasian Economic Union in professional and informal spheres. The article characterizes the real state of interethnic concord as a stable nucleus of the integration process and shows the problems and contradictions that reduce ethnic complementarity of interethnic relations, empathy, and support for integration processes in the Eurasian Economic Union.